Core outcomes for pressure ulcer prevention trials: results of an international consensus study. (1st November 2022) - Lechner, Anna; Coleman, Susanne; Balzer, Katrin; Kirkham, Jamie J.; Muir, Delia; Nixon, Jane; Kottner, Jan
Abstract: Background: There is substantial heterogeneity between trial outcomes in pressure ulcer prevention research. The development of core outcome sets is one strategy to improve comparability between trial results and thus increase the quality of evidence. Objectives: To identify core outcomes for pressure ulcer prevention trials. Methods: A workshop was held with service users to discuss their views and understanding of the outcomes identified by a scoping review and to identify any missing outcomes. In a next step, a Delphi survey comprising three rounds was conducted to evaluate a compiled list of outcomes by their importance. Afterwards the preselection from the Delphi survey was discussed in a virtual consensus meeting with the aim of agreeing on a final set of core outcomes. Individuals who had completed all three rounds of the Delphi survey were eligible to participate in this meeting. Participants included practitioners, service users, researchers and industry representatives. The OUTPUTs project is registered in the COMET database and is part of the Cochrane Skin Core Outcome Set Initiative. Results: The workshop did not reveal any missing outcomes, but highlighted the need for further efforts to make lay people understand what an outcome is in a study setting. The Delphi survey took place between December 2020 and June 2021. After the three rounds, 18 out of 37 presented outcomes were rated to be critically important. In the following consensus meeting, six outcomes were prioritized to be included in the core outcome set for pressure ulcer prevention trials: (i) pressure ulcer occurrence; (ii) pressure ulcer precursor signs and symptoms; (iii) mobility; (iv) acceptability and comfort of intervention; (v) adherence/compliance; and (vi) adverse events/safety. Conclusions: Based on a comprehensive list of outcomes in pressure ulcer prevention research, there was clear agreement on the six identified core outcomes in three international Delphi rounds and in the consensus meeting. Although outcome measurement instruments need to be identified next, the six identified core outcomes should already be considered in future trials, as service users, practitioners, researchers and industry representatives have agreed that they are critically important. What is already known about this topic? There are numerous trials on pressure ulcer prevention, but evidence on the effectiveness of preventive measures is limited due to heterogeneity between trial outcomes. The development of a core outcome set is one strategy to improve comparability between trial results. What does this study add? A service user workshop, a three‐round Delphi survey and an online consensus meeting with practitioners, service users, researchers and industry representatives were conducted to identify core outcomes for pressure ulcer prevention trials. Six core outcomes were defined: (i) pressure ulcer occurrence, (ii) pressure ulcer precursor signs and symptoms, (iii) mobility, (iv) acceptability and comfort of intervention, (v) adherence/compliance and (vi) adverse events/safety. What are the clinical implications of this work? Better evidence of interventions for pressure ulcer prevention will help health professionals and service users to decide which interventions are most appropriate and effective. Better evidence may contribute to better pressure ulcer prevention. Abstract: A service user workshop, a three‐round Delphi survey and an online consensus meeting with practitioners, service users, researchers and industry representatives were conducted to identify core outcomes for pressure ulcer prevention trials. The following six core outcomes were defined: (1) pressure ulcer occurrence; (2) pressure ulcer precursor signs and symptoms; (3) mobility; (4) acceptability and comfort of intervention; (5) adherence/compliance; and (6) adverse events/safety. Linked Comment: A.C. Fledderus and H.A. Gout. Br J Dermatol 2022; 187:634–635 .